Theoretical Concepts of Digital Regulation of Extreme Vibrations in Consumer Demand on the Market of Services - SIMCHENKO, Nataliia Al.; BURKALTSEVA, Diana; TSOHLA, Svetlana; OSMANOVA, Elnara; YANOVSKAYA, Anna; POLSKAYA, Svetlana (Journal of Environmental Management and Tourism; Vol 12 No 4 (2021): JEMT Volume XII Issue 4(52) Summer 2021, 2021)
The COVID-19 pandemic has made significant adjustments to the process of economic reproduction around the world, affecting all sectors of the national economy. The greatest losses were incurred by the entrepreneurial networks of the service sector, and, in particular, the tourist one. The paper considers the trends in the functioning of the tourism industry of the Republic of Crimea, analyzes the measures taken to improve the industry, and also considers the development prospects. The concept of digital development of the Crimean territories based on the implementation of the medical and recreational vector for the development of the region has been developed. The scientific significance of the result is determined by the conceptual support for leveling extreme fluctuations in demand in the market for recreational services.